Ana Wambrechtsamer – pisateljica in povezovalka dveh jezikov in kultur - Čeh Steger, Jožica (Slavia Centralis, 2020)
ANA WAMBRECHTSAMER – WRITER AND BRIDGE BETWEEN TWO LANGUAGES AND CULTURES The contribution discusses the Slovene-German bilingual writer Ana Wambrechtsamer (1897‒1933) and places her within the intercultural model of Slovene literary history. Ana Wambrechtsamer grew up in the bilingual South-Styrian milieu and wrote poems and romance coloured native and historical narratives in German. After moving to Austria, she thoroughly studied the history of the Counts of Cilli and increasingly sought her Slovenian roots. She intensively learnt Slovenian in order to be able to create literature in this language. She also read Slovenian classics, and started translating her works into Slovenian and Slovenian literature into German.
Keywords: intercultural literature; Slovene-German literature in Styria; Ana Wambrechtsamer; native/local literature; historical story; Guzej